Popularization of science: extensionist proposal for the dissemination of studies on headaches and cranial algias - Ramos, Edivan Rodrigo de Paula; Pereira, Luís Fernando Rafalski; Mazzarollo, Thiago Rafael; Cesar, Alcantara Ramos de Assis (Headache Medicine, 2022)
Letter to the editor Popularization of science: extensionist proposal for the dissemination of studies on headaches and cranial algias